PENGARUH MEDIA SOSIAL, KONFORMITAS TEMAN SEBAYA DAN LIFESTYLE TERHADAP BERPERILAKU KONSUMTIF PADA MAHASISWA INSTITUT AGAMA ISLAM TASIKMALAYA - Hindun Hiriyanti; Arip Nugraha, Junjun (LPPM IAIT, 2024)
Many students have social media and actively play social media. Some students can spend more than 3 hours a day accessing social media. The social media they have are Instagram, Tiktok, Whatsapp and they also actively follow the trending lifestyle on social media, and often spend some of their pocket money to buy goods and visit places that are trending on social media. This study aims to determine the effect of the use of social media and lifestyle on the consumptive behavior of students of the Institute of Islam Tasikmalaya.The research method used is quantitative method with data collection techniques through questionnaires. The population in this study were students of the Institute of Islam Tasikmalaya and the sample taken was 116 respondents with purposive sampling technique. Data analysis using multiple linear regression analysis.The findings of this study indicate that social media, peer conformity, and lifestyle are important determinants that influence consumptive behavior among college students. Each of these variables plays a significant role both individually and collectively in encouraging consumptive behavior. The implication of the results of this study is the importance of awareness of social and lifestyle influences on consumption behavior, which can be used by marketers in devising more effective marketing strategies, as well as by individuals to understand the dynamics behind their consumption decisions.